Genesis of nanostructures formation in amorphous hydrogenated semiconductors A-SI1-X CX: H - Kumekov, M.E. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
On the basis of the analysis of experimental data it is shown that at increase in the maintenance of carbon more, than on 50 % (х from above 0,5) there is a cardinal change of photoluminescent and photo-electric properties thin films а-Si1-XCX:H connected with nanoclusterization the films structures.
Keywords: thin films; nanoclusterization; semiconductors; exciting quantums; structurization